MANTLE ORIGIN OF THE ANTRONA SERPENTINITES (ANTRONA OPHIOLITE, PENNINE ALPS) AS INFERRED FROM MICROSTRUCTURAL, MICROCHEMICAL, AND NEUTRON DIFFRACTION QUANTITATIVE TEXTURE ANALYSIS - Tartarotti, Paola; Zucali, Michele; Panseri, Matteo; Lissandrelli, Sabrina; Capelli, Silvia; Ouladdiaf, Bachir (Ofioliti, 2011)
The Antrona ophiolite is located in the Italian side of Western Central Alps. In the Alpine nappe stack, it lies at low structural levels, being sandwiched between the overlying continental Monte Rosa Nappe (upper Penninic) and the underlying Camughera-Moncucco continental Unit (middle Penninic). The ophiolite sequence includes serpentinized ultramafites, metagabbros and mafic rocks covered by calcschists. The ultramafic portion of the Antrona ophiolite consists of serpentinized peridotites, with interbedded layers of various mafic/ultramafic rocks, and underlies the mafic rocks and metasediments. In spite of the Alpine tectonic and metamorphic evolution of the Antrona ophiolite and its heavy serpentinization, the ultramafic rocks preserve relict texture and mineralogy that allow discussing the nature of their protoliths. Olivine-clinopyroxene-spinel-bearing serpentinites still retain relict porphyroclastic texture, commonly attributed to mantle peridotites. This inference is supported by quantitative textural analysis of Lattice Preferred Orientation by neutron diffraction, performed for the first time in olivine crystals of Alpine ophiolites, suggesting T conditions > 800°C for the activation of slip systems. Mineral chemistry of fresh olivine, clinopyroxene and spinel also contribute to support the mantle nature of the serpentinite protolith. The Antrona ophiolite may thus be regarded as a fossilized fragment of oceanic lithosphere including mantle rocks, volcanics and deep-see sediments. Although their extention is smaller, the Antrona ophiolite seems to be comparable with a coherent ophiolitic slice, such as Zermatt Saas ophiolite more than with a serpentinite mélange.